PRIMARY LYMPH NODE HEMANGIOMA IN A PATIENT WITH INVASIVE DUCTAL CARCINOMA - Sarris, Andrey Biff; Matnei, Thiago; Candido, Fernando Jose Leopoldino Fernandes; Fernandes, Luiz Gustavo Rachid; Calil, Sadi Martins; Montemor Netto, Mário Rodrigues (Mastology, 2018)
Primary lymph node hemangioma is a rare entity with only a few cases having been reported in the literature. This article describes a case of a 68-year-old female patient with breast cancer who underwent modified radical mastectomy with a subsequent histopathological evaluation that revealed invasive ductal carcinoma histological grade III according to Nottingham’s Combined Classification. Among the 14 resected lymph nodes, the presence of vascular proliferation (intranodal) was observed in one of them, consistent with primary nodal hemangioma. Thus, knowledge about this clinical entity is important in order to establish the correct differential diagnosis with malignant primary neoplasms and metastasis, in which therapeutics and prognosis are very different.